Social Media Influencers, Brand Awareness, and Brand Image on Purchasing Decisions for Skincare Products - Febriyanti, Endah; Fajri, Annisa (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the effect of social media influencers, brand awareness, and brand image on purchasing decisions for skincare products in Semarang City. The results of this study indicate that partially there is a positive and significant influence on Social Media Influencers, Brand Awareness, and Brand Image on Purchasing Decisions on Skincare Products. Also, the results of the study explain that simultaneously there is a positive and significant influence of Social Media Influencers, Brand Awareness, and Brand Image on Purchasing Decisions on Skincare Products. The results of the coefficient of determination test with a value of 0.789 which means that the amount of Social Media Influencers, Brand Awareness, and Brand Image on Purchasing Decisions is 78.9%, while the remaining 21.1% is influenced by other factors not included in this study.